2002
DOI: 10.1037/0097-7403.28.3.309
|View full text |Cite
|
Sign up to set email alerts
|

Intraadministration associations: Conditional hyperalgesia elicited by morphine onset cues.

Abstract: There is evidence that exteroceptive cues associated with drug administration elicit conditional compensatory responding (e.g., hyperalgesia in organisms with a history of morphine administration). Recently it has become apparent that, within each administration, interoceptive early-drug onset cues (DOCs) may become associated with the later, larger drug effect (intraadministration associations). The present experiments evaluated DOC-elicited conditional hyperalgesia in rats intravenously infused with morphine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
49
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(50 citation statements)
references
References 33 publications
1
49
0
Order By: Relevance
“…Adams and Holtzman (1990) had suggested conditioning to the interoceptive stimulus properties of opioid antagonists, wherein the interoceptive cues associated with low doses of the antagonist in the cumulative dose-effect function acquire predictive value of the withdrawal state elicited by the higher doses that follow later in the session. Siegel and colleagues (Sokolowska et al 2002) have similarly argued that interoceptive cues can contribute to other conditioned drug responses, such as conditioned hyperalgesia to morphine. The current data in which extra naloxone experience resulted in potentiation of naloxone potency only when extra experience was associated with the operant context would suggest that any predictive value of interoceptive antagonist cues is acquired in a contextspecific fashion.…”
Section: Effects Of Varying Context In Which Naloxone Is Experienced mentioning
confidence: 99%
“…Adams and Holtzman (1990) had suggested conditioning to the interoceptive stimulus properties of opioid antagonists, wherein the interoceptive cues associated with low doses of the antagonist in the cumulative dose-effect function acquire predictive value of the withdrawal state elicited by the higher doses that follow later in the session. Siegel and colleagues (Sokolowska et al 2002) have similarly argued that interoceptive cues can contribute to other conditioned drug responses, such as conditioned hyperalgesia to morphine. The current data in which extra naloxone experience resulted in potentiation of naloxone potency only when extra experience was associated with the operant context would suggest that any predictive value of interoceptive antagonist cues is acquired in a contextspecific fashion.…”
Section: Effects Of Varying Context In Which Naloxone Is Experienced mentioning
confidence: 99%
“…The second order, longlasting memory state of morphine sets the opportunity for the encoding of morphine-induced pain in that state; once this encoding is established, subsequent opioid administrations reinstate retrieval (e.g., of pain; Bruins Slot and Colpaert, 1999b,c) and render retrieval increasingly dependent on that state (Bruins Slot and Colpaert, 2003). This statedependent retrieval may explain how subsequent opioid administrations reinstate pain in terms of both its sensory (Sokolowska et al, 2002), and, as here (Fig. 3B), affective/ motivational qualities (i.e., in a CPP paradigm; Mueller et al, 2002).…”
Section: -Htmentioning
confidence: 99%
“…Opioid pain occurs even upon single administration and can be conditioned to "morphine onset cues" to cause intra-administration associations (Sokolowska et al, 2002). Indeed, previous experience with heroin in withdrawal-at a time that opioid pain likely prevails-is necessary for subsequent heroin-seeking behavior to be enhanced when rats again experience withdrawal (Hutcheson et al, 2001).…”
Section: -Htmentioning
confidence: 99%
“…The method in these experiments consisted of giving a low dose of a drug, paired with a subsequent larger dose of the same drug. These studies have demonstrated acquisition and extinction effects when the low dose of the drug served as the CS (Cepeda-Benito & Short, 1997;Greeley, Lê, Poulos, & Cappell, 1984;Kim, Siegel, & Patenall, 1999;Sokolowska, Siegel, & Kim, 2002). However, these experiments have not compared the relative effectiveness of arbitrary versus drug cues as signals for subsequent drug administration and have not examined such manipulations as blocking, CS-US interval effects, or second-order conditioning.…”
Section: Us-us Versus Cs-us Learningmentioning
confidence: 99%